Strategy of Finance Service Development in the Field of Collecting and Recycling Solid Municipal Waste in Regions of the Russins Federation - A. A. Garnova (Вестник Российского экономического университета имени Г. В. Плеханова)
An acute problem facing today’s society is collecting and recycling solid municipal waste (SMW). The author studies this problem on the basis of the growing speculative factor dealing with enormous amount of poorly used SMW and shortage of budget funds for their efficient management and recycling.   The goal of the article is to work out effective strategies to raise investment to this field and to raise finance stability of the system of SMW collecting and recycling.   To reach this goal the author proposes to analyze the current condition of the industry, study best practices of international and Russian companies and identify hindrances and challenges that bar the development of finance services in the sector. It should be mentioned that successful development of finance services in the field of SMW collecting and recycling requires a complex approach including not only elaboration of new finance mechanisms but instructing people for principles of separate collecting and recycling waste and upgrading technologies of SMW recycling and utilization.